Pursuing global socio-economic, colonial and environmental justice through economic redistribution: the potential significance of human rights treaty obligations - Ralph Wilde (Edward Elgar Publishing, 2020)
This comprehensive Research Handbook offers a comparative overview of the history, nature and current status of social rights at the universal and regional level. Tracing their evolution from rather modest beginnings, to becoming the category of rights responding most accurately to the 21st century's policy objectives of poverty eradication and equitable resource allocation, this Research Handbook assesses the mechanisms used to enhance the implementation and enforcement of social rights.